The Role of Additional Book Reading Programs on Students’ Metacognitive Awareness of Reading Strategies - faramarz soheili; zahra solgi; ziba mimanatabadi (تحقیقات اطلاع‌رسانی و کتابخانه‌های عمومی, 2021)
Purpose: The purpose of this study is to determine the role of additional book reading programs (‘Ketabkhan’ reading sessions, school reading sessions, and group reading sessions) on metacognitive awareness of reading strategies (global reading, support reading, and problem-solving reading) of high school students in the city of Sahneh, located in Kermanshah, Iran. Method: This research is a semi-experimental study using pretest-posttest design with three test groups and one control group. The research population included all female high school students (first to fourth grade) in the city of Sahneh in the academic year 2017-2018 )1397-1396(, whose total number was 1098. In this research, cluster random sampling was used to determine the sample size. 60 students who had criteria for entering the research were selected. The data collection tool was a metacognitive standard awareness questionnaire drawn from the reading strategies of Mokhtari and Richard (2002). Validity of the questionnaire was confirmed by a group of psychology and Knowledge and Information science professors. The reliability scores of the questionnaire for the subscales of the global reading strategies, support reading strategies, and problem-solving reading strategies were 0.733, 0.829 and 0.771, respectively. Findings: The findings of this study showed that in the ‘Ketabkhan’ reading session group, the mean score of metacognitive awareness of reading strategies in general and its components after intervention was significantly higher than before. In the school reading session group, the mean scores of meta-cognitive awareness of reading strategies in general and its components before and after intervention were not significantly different. In the group reading session group, the mean score of metacognitive awareness of reading strategies in general and its components after intervention was significantly higher than before. The findings also indicated that both methods of ‘Ketabkhan’ reading session and group reading had significant positive effect on the components of global reading, support reading, and problem-solving reading. Originality/value: Book reading additional programs can make students’ metacognitive awareness of reading strategies more effective and efficient. With regard to these programs that can be applied in educational centers (at all levels), educational and cultural institutions of the country should have a thorough and coherent planning in this area.